2022
DOI: 10.3390/cancers14061477
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Treatments for Metastatic Gastrointestinal Stromal Tumor in British Columbia: A Retrospective Cohort Study from January 2008 to December 2017

Abstract: Introduction: The role of surgery and non-surgical locoregional treatments (LRT) such as radiation therapy (RT) and local ablation techniques in patients with metastatic gastrointestinal stromal tumor (GIST) is unclear. This study examines LRT practice patterns in metastatic GIST and their clinical outcomes in British Columbia (BC). Methods: Patients diagnosed with either recurrent or de novo metastatic GIST from January 2008 to December 2017 were identified. Clinical characteristics and outcomes were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Through the analysis of symptomatic GISTs, we found that the symptom palliation rate of radiotherapy alone and radiotherapy with concomitant previously resistant TKIs reached 78.6% (22/28), which supports the application of radiotherapy in GISTs for palliative purposes recommended by the guidelines [2]. In addition to pain, radiotherapy may also be used to relieve the symptoms of bleeding and spinal cord compression [51,53]. Patterson et al reported that among 12 patients with advanced or metastatic GISTs treated by radiotherapy, 9 had improvement in symptoms to varying degrees [53].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Through the analysis of symptomatic GISTs, we found that the symptom palliation rate of radiotherapy alone and radiotherapy with concomitant previously resistant TKIs reached 78.6% (22/28), which supports the application of radiotherapy in GISTs for palliative purposes recommended by the guidelines [2]. In addition to pain, radiotherapy may also be used to relieve the symptoms of bleeding and spinal cord compression [51,53]. Patterson et al reported that among 12 patients with advanced or metastatic GISTs treated by radiotherapy, 9 had improvement in symptoms to varying degrees [53].…”
Section: Discussionsupporting
confidence: 60%
“…In addition to pain, radiotherapy may also be used to relieve the symptoms of bleeding and spinal cord compression [51,53]. Patterson et al reported that among 12 patients with advanced or metastatic GISTs treated by radiotherapy, 9 had improvement in symptoms to varying degrees [53]. However, all 12 patients received TKIs during radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic GIST are currently treated with oral KIT and PDGFR tyrosine-kinase inhibitors (TKI) such as imatinib, sunitinib and regorafenib [2][3][4]. Over two decades, significant changes in drug discovery and locoregional (LR) procedures have impacted treatment strategies [5][6][7][8]. Recently, two new drugs have been approved in metastatic GIST, namely ripretinib after failure of at least three lines, including imatinib [9], and avapritinib in GIST with the PDGFRA exon 18 D842V mutation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two new drugs have been approved in metastatic GIST, namely ripretinib after failure of at least three lines, including imatinib [9], and avapritinib in GIST with the PDGFRA exon 18 D842V mutation [10]. However, data about real-life multimodal treatment strategies and their outcomes for patients with metastatic GIST are limited [8].…”
Section: Introductionmentioning
confidence: 99%